Treatment of chronic osteomyelitis with gradient release of DGEA and vancomycin hydrogel-microsphere system and its mechanism - Zheng, Yuhao; Wang, Yue; Sheng, Fan; Wang, Shu; Zhou, Ying; Li, Xiaoxu; Li, Ning; Song, Wenling; Song, Zhiming (Frontiers in Pharmacology, 2024)
In recent years, the treatment of chronic osteomyelitis mediated by biodegradable polymer platforms has received increasing attention. This paper reports an advanced drug delivery system, vancomycin (VA) and DGEA loaded microspheres embedded in injectable thermosensitive polypeptide hydrogels (i.e., hydrogelmicrosphere (Gel-MP) construct), for continuous release of drugs with different mechanisms and more comprehensive treatment of chronic osteomyelitis. The Gel-MP construct exhibits continuous biodegradability and excellent biocompatibility. Microspheres (MP) are wrapped inside Gel. With the degradation of Gel, VA and MP are released from them, VA released with faster degradation speed, achieving a potent antibacterial effect and effectively controlling infection. Due to the slower degradation rate of MP compared to Gel, subsequently, DGEA is released from MP to induce bone formation and produce the effect of filling bone defects. Compared with other formulations, the in vivo combinational treatment of Gel/VA-MP/DGEA can simultaneously balance antibacterial and osteogenic effects. More importantly, local sustained-release drug delivery systems can significantly mitigate the systemic toxicity of drugs. Therefore, the injection local sequential drug delivery system has broad prospects in the clinical application of treating chronic osteomyelitis.